INTERSECTING FORMS OF VIOLENCE AND TRAUMA IN KATHLEEN GLASGOW’S GIRL IN PIECES: A LITERARY-SOCIOLOGICAL ANALYSIS OF FEMALE MENTAL HEALTH - Surayya MS, Malisa; Anayati, Wan; Purwarno, Purwarno (JOURNAL OF LANGUAGE, 2025)
This article analyzes the complex representation of violence and trauma in Kathleen Glasgow’s Girl in Pieces, focusing on the protagonist Charlie Davis. Through Johan Galtung’s violence typology—direct, structural, and symbolic—the study reveals how Glasgow constructs an emotionally resonant narrative of trauma that is deeply rooted in systemic and interpersonal failures. Charlie’s self-harm, institutional neglect, and internalized shame illustrate how violence is experienced not only through physical abuse but also through social and cultural mechanisms. The research applies a sociological approach to literature and trauma theory, situating the novel within the broader context of Young Adult (YA) fiction that foregrounds psychological suffering. This approach reveals that Girl in Pieces is not merely a coming-of-age story but a social critique of how institutions respond to marginalized female trauma. Using qualitative content analysis, the article contributes to discussions in trauma-informed literary pedagogy and young adult mental health literature. Findings suggest that literature, when interpreted through a sociological and trauma-sensitive lens, holds critical potential for reshaping understandings of mental illness, recovery, and gendered pain. The study supports the integration of trauma narratives into educational spaces as a means to foster empathy, awareness, and policy reform around youth mental health.